Ambient extreme heat exposure in summer and transitional months and emergency department visits and hospital admissions due to pregnancy complications - Qu, Yanji; Zhang, Wangjian; Ryan, Ian; Deng, Xinlei; Dong, Guanghui; Liu, Xiaoqing; Lin, Shao (The Science of the total environment, 2021)
Although extreme heat exposure (EHE) was reported to be associated with increased risks of multiple diseases, little is known about the effects of EHE on pregnancy complications. We examined the EHE-pregnancy complications associations by lag days, subtypes, sociodemographic characteristics, and areas in New York State (NYS). We conducted a case-crossover analysis to assess the EHE-pregnancy complications associations in summer (June–August) and transitional months (May and September). All emergency department (ED) visits and hospital admissions due to pregnancy complications (ICD 9 codes: 630–649) from 2005 to 2013 in NYS were included. Daily mean temperature > 90th percentile of the monthly mean temperature in each county was defined as an EHE. We used conditional logistic regression while controlling for other weather factors, air pollutants and holidays to assess the EHE-pregnancy complications associations. EHE was significantly associated with increased ED visits for pregnancy complications in summer (ORs ranged: 1.01–1.04 from lag days 0–5). There was also a significant and stronger association in transitional months (ORs ranged: 1.02–1.06, Lag 0). Furthermore, we found EHE affected multiple subtypes of pregnancy complications, including threatened/spontaneous abortion, renal diseases, infectious diseases, diabetes, and hypertension (ORs range: 1.13–1.90) during transitional months. A significant concentration response effect between the number of consecutive days of EHE and ED visits in summer (P for trend <0.001), ED visits in September (P for trend =0.03), and hospital admission in May (P for trend<0.001) due to pregnancy complications was observed, respectively. African Americans and residents in lower socioeconomic position (SEP) counties were more susceptible to the effects of EHE. In conclusion, we found an immediate and prolonged effect of EHE on pregnancy complications in summer and a stronger, immediate effect in transitional months. These effects were stronger in African Americans and counties with lower SEP. Earlier warnings regarding extreme heat are recommended to decrease pregnancy complications. [Display omitted] •EHE posted an immediate and prolonged effect on pregnancy complications in summer.•The effect of EHE was immediate, but stronger in transitional months than in summer.•EHE was associated with increased risk of common subtypes of pregnancy complications.•The effect of EHE was stronger among African Americans and in lower SES counties.